Revealing the New Identity Element to Construct Palembang City Branding - Rahma Santhi Zinaida; Sunarto Sunarto; Manik Sunuantari (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2022)
More than just selling, a city must be constructed as an image formation process, which is formed from a mental map created by local people that produces an original identity to make a good branding. This research aims to reveal a new element of city identity and produce a mapping process of forming a strong city identity based on the advantages of the city that can be used in perfecting the concept of city branding. The result shows that the natural appearance in this study refers to the appearance of the river and the surrounding area called “RIVERINE” which means the area around the river. These elements also become the identity of Palembang and can be one of the elements to construct a concept of city branding. The research’s state-of-the-art findings are the new element to constructing the city identity of Palembang by revealing the role of the new element of city identity construction.